INVESTIGATING LEARNER AUTONOMY IN A TOEFL PREPARATION PROGRAM - Nurul Noviana; Priyatno Ardi (STKIP Persada Khatulistiwa Sintang, 2020)
Learner autonomy is learners’ ability to take charge, set the rules and style of their learning as the goals. Profiling autonomous learners can be seen in the TOEFL preparation program class. TOEFL preparation program is a course subject to provide learners in achieving the TOEFL score target to fulfill requirements as ELT students. The class provides learners with more opportunities in studying pre-face-to-face sessions by giving the students worksheets. These opportunities directed the learners to exercise their English. This study investigates the learning activities conducted by EFL learners in the TOEFL class and the use of learner autonomy in the pre-face-to-face session in the TOEFL preparation program. The study employed a qualitative narrative inquiry, grounded in phenomenological research. Data were collected and analyzed qualitatively by understanding the meaning of lived experiences. Data were gathered by interviewing 5 participants and observing the TOEFL class. Based on the findings, there were numbers of extension language activities held by the learners. There were five themes categories of learner autonomy as strategy, learner autonomy as perceptions, learner autonomy as behavior, learner autonomy as the interdependence of social autonomy, and experiences from learning TOEFL test preparation program in learners’ lived experiences.